Environmental Issues During Clearing Quarry Waters Madneuli Mining Concentration Enterprise - Andguladze, Shalva N.; Gaphrindashvili, Vakhtang N.; Andguladze, Nikoloz Sh. (Journals of Georgian Geophysical Society, 2017)
The use of the elaborated technology enables to use low-graded barite ore by processing of which is acquired the independent product blanfix and sodium sulfide used as a reagent of non-solvent for deep purification of the acid quarry waters from ions of heavy metals with obtaining sulfide copper containing compounds fully useful for subsequent application.